Welfare Effects of Uzbekistan's Foreign Exchange Regime. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
In addition to transferring about 16 percent of GDP from exporters to importers, Uzbekistan's quasi-fiscal multiple exchange rate regime generates identifiable welfare losses of 2-8 percent of GDP on import markets and up to 15 percent on export markets. These excess burdens have increased substantially with the growing difference of exchange rates. The welfare analysis allows some conclusions regarding the optimal reform strategy: (i) welfare losses will decline overproportionally as exchange rates unify; (ii) exchange rate unification should be supplemented by changing the explicit fiscal system; (iii) at a minimum, Uzbekistan would benefit from moving to an explicit fiscal regime.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet